Challenging Anzac myths in tertiary teaching: Engaging preservice teachers - Ford, Margot; Bennett, James; Kilmister, Michael (Journal of University Teaching and Learning Practice, 2019)
Challenging the embedded mythologies that surround Anzac, especially as the centenary of First World War played out over the 2014 to 2018 commemoration period, can be confronting for tertiary students as well as a difficult space for tutors to navigate. This is especially the case for teacher education students who form the majority cohort taking a first-year course in Australian History as part of their teaching education degree programs at a large New South Wales university outside Sydney. Experiences of student disruptions, confrontations and occasional anger prompted tutors to question whether the topic of Anzac should be covered at all. An alternative was sought, where careful interrogation of teaching practices was undertaken. Three pedagogical approaches were examined; the traditional lecture format, using documentary film to glimpse at deeper historiographical problems within lectures and tutorials that allowed for more intense critical thinking and analysis of historical resources via focused questions.The efficacy of these pedagogical approaches was systematically assessed through surveying students in the Australian History course prior and post teaching about Anzac. This paper examines the background of teaching Anzac in the tertiary space, the use of specific pedagogical approaches and the results of the survey. Students’ main preference for teaching methods about Anzac was through documentaries in both surveys. However, the second most preferred method was the lecture format more generally and this preference increased in the post survey. There was also evidence of less resistance to the contested nature of Anzac mythologies.